Pentraxin 3 Induces Vascular Endothelial Dysfunction Through a P-selectin/Matrix Metalloproteinase-1 Pathway. Issue 17 (28th April 2015) - Carrizzo, Albino; Lenzi, Paola; Procaccini, Claudio; Damato, Antonio; Biagioni, Francesca; Ambrosio, Mariateresa; Amodio, Giuseppina; Remondelli, Paolo; Del Giudice, Carmine; Izzo, Raffaele; Malovini, Alberto; Formisano, Luigi; et al.
<x xml:space="preserve">Abstract</x> Background— Pentraxin 3 (PTX3), the prototype of long pentraxins, has been described to be associated with endothelial dysfunction in different cardiovascular disorders. No study has yet evaluated the possible direct effect of PTX3 on vascular function. Methods and Results— Through in vitro experiments of vascular reactivity and ultrastructural analyses, we demonstrate that PTX3 induces dysfunction and morphological changes in the endothelial layer through a P-selectin/matrix metalloproteinase-1 pathway. The latter hampered the detachment of endothelial nitric oxide synthase from caveolin-1, leading to an impairment of nitric oxide signaling. In vivo studies showed that administering PTX3 to wild-type mice induced endothelial dysfunction and increased blood pressure, an effect absent in P-selectin–deficient mice. In isolated human umbilical vein endothelial cells, PTX3 significantly blunted nitric oxide production through the matrix metalloproteinase-1 pathway. Finally, using ELISA, we found that hypertensive patients (n=31) have higher plasma levels of PTX3 and its mediators P-selectin and matrix metalloproteinase-1 than normotensive subjects (n=21). Conclusions— Our data show for the first time a direct role of PTX3 on vascular function and blood pressure homeostasis, identifying the molecular mechanisms involved. The findings in humans suggest that PTX3, P-selectin, and matrix metalloproteinase-1 may be novel biomarkers that predict the onset of vascular dysfunction in hypertensive patients.